RADIATION EFFICIENCY OF A PERFORATED PANEL MODELLED USING ELEMENTARY SOURCE TECHNIQUE - Putra, Azma; Muhammad, Noryani; Shyafina, Nurain; Thompson, David J. (International Institute of Acoustics and Vibration, 2013)
A perforate is often used in practical engineering noise control to reduce sound radiation from a vibrating structure. This paper presents a prediction model to quantify this effect using elementary sources which can take account of the hole size and distribution across the plate surface. The model is based on discretization of the Rayleigh formula where a plate set in an infinite rigid baffle is divided into array of elementary source. A matrix of acoustic impedance as a function of acoustic pressure due to motion of the corresponding elementary source and other surrounding sources is assembled. The total sound power is determined from the summation over the power contributions from all elementary sources. The results show that the radiation efficiency reduces as the perforation ratio is increased or the hole size is reduced.